Light-emitting quantum dot transistors: emission at high charge carrier densities - Schornbaum, Julia; Zakharko, Yuriy; Held, Martin; Thiemann, Stefan; Gannott, Florentina; Zaumseil, Jana (Nano letters, 2015)
For the application of colloidal semiconductor quantum dots in optoelectronic devices, for example, solar cells and light-emitting diodes, it is crucial to understand and control their charge transport and recombination dynamics at high carrier densities. Both can be studied in ambipolar, light-emitting field-effect transistors (LEFETs). Here, we report the first quantum dot light-emitting transistor. Electrolyte-gated PbS quantum dot LEFETs exhibit near-infrared electroluminescence from a confined region within the channel, which proves true ambipolar transport in ligand-exchanged quantum dot solids. Unexpectedly, the external quantum efficiencies improve significantly with current density. This effect correlates with the unusual increase of photoluminescence quantum yield and longer average lifetimes at higher electron and hole concentrations in PbS quantum dot thin films. We attribute the initially low emission efficiencies to nonradiative losses through trap states. At higher carrier densities, these trap states are deactivated and emission is dominated by trions.
Gesehen am 13.07.2020